Green, circular, bio economy: A comparative analysis of sustainability avenues. (1st December 2017) - D'Amato, D.; Droste, N.; Allen, B.; Kettunen, M.; Lähtinen, K.; Korhonen, J.; Leskinen, P.; Matthies, B.D.; Toppinen, A.
Abstract: Despite their evidently different assumptions and operationalization strategies, the concepts of Circular Economy, Green Economy and Bioeconomy are joined by the common ideal to reconcile economic, environmental and social goals. The three concepts are currently mainstreamed in academia and policy making as key sustainability avenues, but a comparative analysis of such concepts is missing. The aim of this article is thus to comprehensively analyse the diversity within and between such concepts. The results are drawn from a bibliometric review of almost two thousand scientific articles published within the last three decades, coupled with a conceptual analysis. We find that, for what concerns environmental sustainability, Green Economy acts as an 'umbrella' concept, including elements from Circular Economy and Bioeconomy concepts (e.g. eco-efficiency; renewables), as well as additional ideas, e.g. nature-based solutions. In particular, Circular Economy and Bioeconomy are resource-focused, whereas in principle Green Economy acknowledges the underpinning role of all ecological processes. Regarding the social dimension, Green Economy is more inclusive of some aspects at local level (e.g. eco-tourism, education), while there is an emerging discussion in Bioeconomy literature around local processes in terms of biosecurity and rural policies. When considering weak/strong sustainability visions, all concepts remain limited in questioning economic growth. By comparing the different sustainability strategies promoted by these concepts we do not advocate for their substitutability, but for their clarification and reciprocal integration. The findings are discussed in light of the concepts' synergies and limits, with the purpose to inform research and policy implementation. Highlights: Circular, Green and Bioeconomy are mainstreamed as global sustainability concepts. They are compared based on a machine-learning analysis of literature. Green economy is more inclusive of social and environmental issues. The concepts are limited in questioning the economic growth paradigm.